How Entrepreneur Personality Affects Agrirural Entrepreneurial Alertness - Chaoyun Liang (Journal of Entrepreneurship, Management and Innovation)
Academic research on agrirural entrepreneurship and opportunity recognition is scant. Because of this research gap, a series of three studies were conducted to develop a measure of entrepreneurial alertness (EA) in agrirural environments that is empirically valid and easy to administer and to analyze how the personality traits of agrirural entrepreneurs affect their EA. The results indicated that both extroversion and openness affected all of the dimensions of EA, whereas conscientiousness only affected scanning and searching and agreeableness only affected evaluation and judgment. The results also demonstrated interactive relationships between extroversion and openness for all of the dimensions of EA. Our results provide a new understanding of how agrirural EA can be assessed more practically and how personality traits can predict various dimensions of agrirural EA.